Analisis Kausalitas Indeks Pembangunan Manusia Pengangguran Pertumbuhan Ekonomi dan Ketimpangan Pendapatan di Indonesia - Panca Gunawan Putra; Ali Anis; Muhammad Irfan (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to analyze: (1) The causality relationship between unemployment and the human development index, (2) The causal relationship between economic growth and the human development index, (3) The causal relationship between income inequality and the human development index, (4) The causal relationship between economic growth and unemployment, (5) Causality relationship between income inequality and unemployment, (6) Causality relationship between income inequality and economic growth, (7) Long-term and short-term relationship between human development index, unemployment, economic growth and income inequality in Indonesia. The data used is panel data from 34 provinces in Indonesia during the 2011-2020 period. The analytical method used is Panel Vector Error Correction Model (PVECM) and Panel Granger Causality Test. The results of this study indicate that there is a relationship: (1) Two-way causality between unemployment and the human development index, (2) Economic growth to the human development index, (3) Income inequality to the human development index, (4) Economic growth to unemployment, ( 5) Income inequality to unemployment, (6) Income inequality to economic growth, (7) There is a long-term relationship between unemployment and the human development index which has a positive effect, economic growth has a negative effect on the human development index and income inequality on the human development index has a positive effect negative.